TRANSFORMATION OF THE EDUCATIONAL PARADIGM THROUGH OUTCOME-BASED EDUCATION IN THE ERA OF DISRUPTION - Hermansyah; Sundari; Tinuk Triyana; Anam Sutopo; Sutama (El Midad, 2025)
This article aims to analyze the transformation of the education paradigm through the Outcome-Based Education (OBE) approach in response to the demands of the disruption era. The main problem studied is the mismatch between the traditional educational paradigm, oriented toward process and material, and the competency needs of the 21st century, which demand that graduates be adaptive, competent, and relevant to the world of work. This research uses a library research approach by conducting a critical review of library sources, including journals, books, educational policies, and previous research results, relevant to the implementation of OBE. The results of the study show that OBE can provide a new direction for the education system through an outcome-based curriculum, active learning, authentic assessments, and a shift in educators’ roles from teachers to facilitators. However, the implementation of OBE also faces various obstacles, including educators’ limited understanding, the dominance of lecture methods, unpreparedness for assessments, and weak institutional support. This article emphasizes that implementing OBE requires structured curriculum design, educator training, the integration of learning technologies, collaboration with industry, and a continuous evaluation system to address educational challenges in the era of disruption